Emerging Technologies for Emerging Markets - Vong, John (Springer, 2015)
This book introduces inclusive-cost-effective (ICE) approaches that have the potential to transform all aspects of daily lives of people at the base of the pyramid in the economic scale, who represent more than 75% of the world population. ICE means that the approaches must meet the affordability level at the base of the pyramid. This includes mobile banking and financial service technologies, mobile education, rural information and communication technologies, telemedicine, e-Health, and health social networks. This monograph is a compulsory reading for not only technology innovators, but also economists, social entrepreneurs, development specialists, health specialists, bankers and researchers and policy thinkers on technology and economic development.